William Blake’s Newton as Innovative Iconography - Noel, Caleb Paul (URJ-UCCS: Undergraduate Research Journal at UCCS, 2015)
Scott Berkun's 2010 bestselling book "The Myths of Innovation" casts the famed scientist Isaac Newton as one of many great thinkers who solved dilemmas no one else saw as problems. During his life, Newton established the idea that mathematical laws rather than spiritual intervention frame the world around us. Berkun uses William Blake's 1795 print "Newton" in relation to the scientist’s innovative prowess, and in doing so, casts the print as an icon of innovation. This use of "Newton" is surprising, since Blake created it as a mockery of Newtonian theory. This paper will explore how Newton was transformed into an icon of innovation despite Blake's intended meaning. It will look at Blake's unique form of spirituality in relation to his innovative engraving process, as well as Eduardo Paolozzi's 1995 sculpture "Newton". After William Blake and how the work has helped to frame the original print in its innovative role.